Applications of TOPSIS Algorithm on various Manufacturing Processes: A Review. (2017) - Shukla, Atul; Agarwal, Pankaj; Rana, R.S.; Purohit, Rajesh
Abstract: Different Manufacturing Processes Optimized by Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) Algorithm are presented in this review paper. The main focus of this review paper is on the optimization of the various manufacturing processes that have been optimized by TOPSIS method. The machining processes that have been considered in this work are Milling, Drilling, Turning, Electric Discharge Machining, Abrasive Jet Machining, Micro Machining, and other advanced types of machining process. The review work on manufacturing processes, on such a large scale was not performed earlier by considering different processes at a time on TOPSIS method, and hence, this review work prepare for the future information at one place for the subsequent researchers, in order to determine their way of research on TOPSIS Algorithm.